Encountering Boris Starck: emotions in legal literature - Veleanu, Corina (2025)
Emotions have become a more prominent topic in legal literature and neuroscientists have been studying the impact cultural emotions have on the organization of human societies for more than twenty years. For jurilinguists and legal translators, language, culture and law are inseparable in our “society of affects”. Studying the work of legal scholars may also shed light on the manner in which emotions are taken into account and explored in relation to the overall economy of their writings and ideas. This paper proposes an affective jurilinguistics approach of the topic of perspective and emotions in a non-fictional narrative genre, legal doctrine, through the concrete example of the writings of B. Starck, a French legal scholar and civil law professor, whose work has not been the object of in-depth study so far. Exploring the reactions produced by legal discourse within the community of legal experts reveals the scope of perspective, or point of view, within a given discourse, as well as the relationship established inside and outside the narrative. The emotions related to and expressed through moral stances and rhetorical techniques such as humor and metaphors underline B. Starck’s philosophy which places human beings at the center of his legal thinking, emphasizing the fact that laws are created to serve and ensure the smooth running of a society that respects everyone.